Stress, emotional eating, snack consumption, energy and fat intake, and body mass index of students during COVID-19 pandemi - Novelita Hanauli; Vitria Melani; Laras Sitoayu; Yulia Wahyuni; Harna Harna (AcTion: Aceh Nutrition Journal, 2024)
The COVID-19 pandemic limits individual activities which causes changes in people's lifestyles, including intake, eating behavior and unstable emotional changes. This condition will have an impact on health, one of which is the individual's nutritional status. This study aims to analyze the correlation among stress, emotional eating, snack consumption, energy and fat intake, and body mass index of students during COVID-19 pandemic. The   design   of   this   study   was cross sectional design. This research was conducted on August-September 2022  with a total sample of 66 people at Universitas Esa Unggul, West Jakarta with proportional stratified random sampling. Retrieval of stress data using the PSS questionnaire, emotional eating using the EEQ questionnaire, snack consumption frequency using FFQ, energy and fat intake using Recall 2x24 hour. The association were analyzed by Spearman Rank correlation test. The results stated that there wasa relationship between energy intake (p = 0,026), fat (p= 0,004) with BMI of students, There was no correlation between stress (p= 0,696), emotional eating (p= 0,242), and frequency of snack consumption (p= 0,278) with student BMI. There is no relationship between stress, emotional eating, and frequency of snack consumption with student BMI during the COVID-19 pandemic. Conclusion: there was an association between energy and fat intake with BMI of students. There was no association between stress, emotional eating (p=0,242), and frequency of snack consumption with student BMI during the COVID-19 pandemic.